1985
DOI: 10.1210/endo-116-2-671
|View full text |Cite
|
Sign up to set email alerts
|

Specific Receptors for Vasopressin in the Pituitary Gland: Evidence for Down-Regulation and Desensitization to Adrenocorticotropin-Releasing Factors

Abstract: Specificity of binding of 3H-labeled arginine vasopressin [( 3H]AVP), down-regulation of receptors, and desensitization were studied in anterior pituitary glands of both Wistar and Brattleboro rats. Studies using both crude membrane fractions and isolated cells of anterior pituitaries revealed the presence of a single population of binding sites with a Kd of approximately 1 nM. The receptor recognized the following peptides, with AVP = lysine vasopressin = vasotocin greater than oxytocin = 1-deamino-(8-D-AVP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
3

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 15 publications
5
31
3
Order By: Relevance
“…Finally, pituitary desensitization to AVP may occur (similar to what has been shown for CRF in in vivo animal studies) independently of any steroid feedback (45). The anterior pituitary contains specific receptors for AVP which are distinct from those for hypothalamic CRF (46,47), and prior injections of AVP might cause down-regulation of the AVP specific receptor on pituitary cells (47). To determine which, if any, of the explanations is correct will require further study.…”
Section: Discussionmentioning
confidence: 83%
“…Finally, pituitary desensitization to AVP may occur (similar to what has been shown for CRF in in vivo animal studies) independently of any steroid feedback (45). The anterior pituitary contains specific receptors for AVP which are distinct from those for hypothalamic CRF (46,47), and prior injections of AVP might cause down-regulation of the AVP specific receptor on pituitary cells (47). To determine which, if any, of the explanations is correct will require further study.…”
Section: Discussionmentioning
confidence: 83%
“…This affinity shift, however, appears to be limited to the brain since peripheral AVP receptors (kid ney, liver, anterior pituitary) do not show affinity changes in the HO-BB rat compared to the HE-BB rat [27,39], The results on Bmax are comparable to those of Koch and Lutz-Bucher [39] who showed that in the anterior pituitary, the number of recep tors for AVP in the HO-BB rat are also increased, and that AVP treatment (via both acute intravenous injection and osmotic minipumps) can down-regulate AVP receptors to a level similar to those in HE-BB rats.…”
Section: Discussionmentioning
confidence: 90%
“…A few small areas of POMC-positive cells did not seem to have CRH receptors in adjacent slides. Although this could be due to intrinsic variabilities in the two different methods used (i.e., autoradiography vs. in situ hybridization), or to the fact that the adjacent slides are 10 pm apart, it is also possible that some of the POMC cells lack CRH receptors and express receptors for other hypothalamic secretagogues, such as arginine vasopressin, a known stimulator of ACTH secretion [32,33], GR expression is widespread in the anterior pituitary, but their mRNA seems to be most highly concentrated in POMC cells. It is known from animal studies that other pituitary cells, such as lactotropes and somatotropes, are regulated by glucocorticoids, and that prolactin and growth hormone genes contain sequences that can bind the GR [34][35][36].…”
Section: Discussionmentioning
confidence: 99%